Correlation between body composition and disease severity in patients with chronic obstructive pulmonary disease - Jin, Xiaohan; Yang, Yu; Chen, Guangmei; Shao, Yue; Liu, Chang; Li, Rong; Liu, Yazhuo; Zhang, Lichuan (Frontiers in Medicine, 2024)
Background Body composition changes are important extrapulmonary manifestations in chronic obstructive pulmonary disease (COPD) patients. This study aimed to investigate the characteristics of body composition in patients with COPD, and its correlation with disease severity. Methods A total of 105 COPD patients admitted to Zhongshan Hospital affiliated to Dalian University, from May 1, 2021 to January 31, 2023, were included as the COPD group, and 105 subjects without COPD were enrolled as the control group during the same period. According to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) comprehensive assessment indicators, COPD patients were divided into groups: the degree of pulmonary function airflow limitation was grouped according to FEV1%pred; clinical symptoms were grouped according to mMRC scores and CAT scores; the risk of acute exacerbation was divided into low risk and high risk groups. Body composition was measured by bioelectrical impedance analysis (BIA). Results (1) Concerning body composition, the body mass index (BMI), fat-free mass index (FFMI), and angle of phase (PhA) of COPD patients were lower than those of the control group. Extracellular water-to-total body water ratio (ECW/TBW) and extra-to-intracellular water ratio (ECW/ICW) were higher than those of the control group, and the difference was statistically significant (p < 0.05). (2) There were differences in body composition among COPD patients with different severity of disease: FFMI and PhA in the mild/moderate airflow limitation group were higher than those in the severe/very severe airflow limitation group. According to mMRC scores classification, the FFMI and PhA of the less symptomatic group were higher than those of the more symptomatic group, and ECW/TBW and ECW/ICW were lower than those of the more symptomatic group. According to CAT scores classification, FFMI and PhA in the mild/moderate disease group were higher than those in the severe/very severe disease group. The FFMI of the low-risk group was higher than that of the high-risk group, and ECW/TBW was lower than that of the high risk group. (3) Correlation analysis between body composition and disease severity indicators showed that FFMI and PhA were negatively correlated with mMRC scores and CAT scores, and positively correlated with FEV1%pred. ECW/TBW ratio and ECW/ICW ratio were positively correlated with mMRC scores and CAT scores, and negatively correlated with FEV1%pred, and the difference was statistically significant (p < 0.05). Conclusion There are significant differences in body composition between COPD patients and the control group, and there are significant differences in body composition between COPD patients with different severity of disease, with correlations between body composition and severity of disease.